An Evaluation of Portuguese Societal Opinion towards the Practice of Bullfighting - Francisco Javier Diéguez (Animals, 2020)
Bullfighting is a controversial sport that continues to be legally permitted in a number of countries around the world, including Portugal. The spectacle has attracted significant attention from animal protectionist groups for many years because of concerns for animal distress, pain, and suffering during the fights. While there has been strong support for the sport in Portugal in the past, there is a need to study social profiles regarding the acceptability of this sport before a case can be made for changes in regional and national legislation. In this study, Portuguese attendance patterns at bullfights were assessed in addition to public opinions on welfare and ethical aspects of bullfighting, based on demographic variables. Study participants (n = 8248) were largely recruited through Portuguese social media channels (respondents may not be representative of the Portuguese population). Questionnaire data were evaluated by means of frequency tables, multiple correspondence analyses, and a two-step cluster analysis. Most respondents had a negative opinion about bullfighting and perceived that bullfighting had no positive impact on the country. However, while most respondents thought that the bull suffered during bullfighting, the opinion regarding banning bullfighting was far from unanimous. Based on the demographic analysis, the profile of individuals with more favorable responses towards bullfighting were men > 65 years old, of Roman Catholic faith, of low- or high-income levels, from more rural areas of Portugal. Somewhat surprisingly, there was a tendency to favor bullfighting amongst veterinary professionals. We conclude that there were still large pockets of individuals who desire to maintain the practice of traditional bullfighting within Portuguese society, despite recognition of animal suffering during the event.